Estrategias activas para la enseñanza de la lectoescritura en los estudiantes de cuarto año de Educación Básica de la Unidad Educativa “Camino del Inca”, estudios realizados durante el año lectivo 2020 – 2021 en la ciudad de Quito, provincia Pichincha. - Galeas Montezuma, Carmen Rocío (2021)
This educational intervention project was developed with the aim of strengthening the teaching of literacy through the application of active methodological strategies to enhance these skills in students of the Fourth Year of Basic General Education of the Educational Unit "Camino del Inca" , in the city of Quito, Pichincha province, during the 2020-2021 school year. For which, an action research methodology was used, starting from the diagnosis, where it was determined that the students showed deficiencies in the development of literacy skills. For this reason, the design and implementation of active methodological strategies was considered pertinent to promote suitable spaces for meaningful learning and the development of skills in the learner. Through the execution of nine active strategies, it was possible to improve literacy skills through the recognition of the phoneme-grapheme relationship, the composition and decomposition of words into letters and syllables, the execution of didactic games to promote reading comprehension and reading comprehension. writing on students.